Evaluation of cervical cone biopsies for coexpression of p16INK4a and Ki-67 in epithelial cells - Reuschenbach, Miriam; Seiz, Mirjam; Knebel Doeberitz, Christina von; Vinokurova, Svetlana; Sartor, Heike; Kommoss, Friedrich; Schmidt, Dietmar; Knebel Doeberitz, Magnus von (International journal of cancer, 2012)
Diffuse overexpression of p16INK4a in basal and parabasal cells of cervical epithelium is a hallmark of human papillomavirus-mediated transformation. Focal p16INK4a expression is occasionally observed in nondysplastic epithelium. In normal cells, expression of p16INK4a triggers cell cycle arrest. However, cells undergoing transformation in intraepithelial lesions actively proliferate. To prove that the different expression patterns of p16INK4a, i.e., focal versus diffuse, reflect biologically different entities, we hypothesized that p16INK4a-positive cells in epithelia displaying focal p16INK4a expression pattern do not coexpress proliferation-associated Ki-67 protein, while p16INK4a-positive cells in lesions with diffuse p16INK4a expression may do. A total of 138 cervical cone biopsies were stained for the expression of p16INK4a and Ki-67 using a primary antibody cocktail. All metaplastic lesions (n = 21) displayed focal staining for p16INK4a, and in all of these lesions p16INK4a-positive cells were found to be negative for Ki-67 expression. Diffuse expression of p16INK4a was observed in 12/21 (57.1%) cervical intraepithelial neoplasia (CIN) 1 lesions, all of them simultaneously showed Ki-67 immunoreactivity in a large proportion of p16INK4a-positive cells. Seventeen of 23 (73.9%) CIN2 lesions and all 27 (100%) CIN3/carcinoma in situ (CIS) as well as all 46 (100%) carcinoma cases displayed diffuse and combined expression of p16INK4a and Ki-67. Coexpression of Ki-67 and p16INK4a in the same cell is entirely restricted to cervical lesions displaying diffuse p16INK4a expression, whereas in lesions with focal p16INK4a expression, p16INK4a-expressing cells are negative for Ki-67. Thus, diffuse expression of p16INK4a reflects lesions with proliferation-competent cells, while p16INK4a-expressing cells associated with focal expression patterns are cell cycle arrested.